The "STARS" study: advanced preoperative rehearsal and intraoperative navigation in neurosurgical oncology - Perin, Alessandro; Gambatesa, Enrico; Rui, Chiara B; Carone, Giovanni; Fanizzi, Claudia; Lombardo, Francesca M; Galbiati, Tommaso F; Sgubin, Donatella; Silberberg, Hagit; Cappabianca, Paolo; Meling, Torstein R; DI Meco, Francesco (Journal of neurosurgical sciences, 2023)
BACKGROUND: Neurosurgical 3D visualizers and simulators are innovative devices capable of defining a surgical strategy in advance and possibly making neurosurgery safer by rehearsing the phases of the operation beforehand. The aim of this study is to evaluate Surgical TheaterTM (Surgical Theater LLC, Mayfield, OH, USA), a new 3D neurosurgical planning, simulation, and navigation system, and qualitatively assess its use in the operating room. METHODS: Clinical data were collected from 30 patients harboring various types of brain tumors; Surgical TheaterTM was used for the preoperative planning and intraoperative 3D navigation. Preoperative and postoperative questionnaires were completed by first and second operators to get qualitative feedback on the system's functionality. Furthermore, we measured and compared the impact of this technology on surgery duration. RESULTS: Neurosurgeons were overall satisfied when using this rehearsal and navigation tool and found it efficient and easy to use; interestingly, residents considered this device more useful as compared to their more senior colleagues (with significantly higher scores, P<0.05), possibly because of their limited anatomical experience and spatial/surgical rehearsal ability. The length of the surgical procedure was not affected by this technology (P>0.05). CONCLUSIONS: Surgical TheaterTM system was found to be clinically useful in improving anatomical understanding, surgical planning, and intraoperative navigation, especially for younger and less experienced neurosurgeons.
Keywords: Neurosurgery; Neurosurgical Procedures; nádory mozku; neurochirurgové; Humans; Neurosurgeons; Brain Neoplasms; neurochirurgické výkony; neurochirurgie; lidé